Factors Affecting the Financial Distress Conditions of Property and Real Estate Companies During the Covid-19 Pandemic Period 2019 – 2021 - Athila Namira Awandini; Hadi Pramono; Iwan Fakhruddin; Nur Isna Inayati (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to find out and obtain empirical evidence of the influence of factors represented by liquidity, leverage, cash flow, and sales growth on financial distress conditions in property and real estate companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used was purposive sampling technique in order to obtain a sample of 113 companies that met the criteria. The data analysis technique used is multiple regression. The results of this study indicate that liquidity has a positive effect on financial distress. Meanwhile, leverage has a negative effect on financial distress. Cash flow and sales growth have no effect on financial distress.